New options and insights for survivable transport networks. - Grover, W.; Doucette, J.; Clouqueur, M.; Leung, D.; Stamatelakis, D. (IEEE Communications magazine)
This article is devoted to a selection of recent topics in survivable networking. New ideas in capacity design and ring-to-mesh evolution are given, as well as a systematic comparison of the capacity requirements of several mesh-based schemes showing how they perform over a range of network graph connectivity. The work provides new options and insights to address the following questions. How does one evolve from an existing ring-based network to a future mesh network? If the facilities graph is very sparse, how can mesh efficiency be much better than rings? How do the options for mesh protection or restoration rank in capacity requirements? How much is efficiency increased if we enrich our network connectivity? We also outline p-cycles, showing this new concept can realize ring-like speed with meshlike efficiency. The scope is limited to conveying basic ideas with an understanding that they could be further adapted for use in IP or DWDM layers with GMPLS-type protocols or a centralized control plane